Оценка физического развития детей как предварительный этап диагностики нарушений, связанных с внутриутробным воздействием этанола на плод - E. V. Fadeeva; A. Yu. Nenastieva; G. A. Korchagina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The fetal alcohol spectrum of disorders (FASD) combines a number of congenital developmental disorders in children who were exposed to intrauterine alcohol, and is represented by mental, behavioral, intellectual, physical and other disabling disorders that persist throughout life. The aim of the study is to test methodology of actively identifying cases of morpho-anatomical and cognitive impairment that arose as the result of fetal effects of alcohol, and to assess prevalence of such disorders in children of primary school age in one of the administrative centers of the Russian Federation. The study was divided into three phases. The article describes the results of the first stage — screening of primary schoolchildren to identify and assess severity of their lag in physical development arising due to prenatal exposure to ethanol. Physical indicators based on the results of accurate measurement of height, weight and calculation of the body mass index of the child were compared to standard indicators taking into account the age and gender of the children. During screening of 2,763 school students, 77 (2.8%) with physical development retardation were found. Among those: 9 (11.7%) had severe physical development retardation — height and weight were below the 3rd centile of age norm indicators; 16 (20.8%) had moderate physical development retardation — both or one indicators (height and/ or weight) were below the 3rd centile of age norm indicators; 52 (67.5%) had minor violations / physical development retardation — one or both indicators (height and/or weight) were at the 10th centile of age norm indicators. All children who had physical development retardation were referred for further diagnostics, in order to identify dysmorphological and cognitive impairments typical for FASD.